Gaining insight in the analysis of performance for Resource Monitoring and Discovery in Grids - González Márquez, D. (2011)
Nowadays, many High Performance Computing (HPC) centers with thousands of cores are available. The interconnection and synchronization between them is one of objectives of Grid Computing, as all these centers tend to form a global shared computing facility. In such scenario, dynamics of resource information is increasingly complex, and may become almost impossible to be captured using a static hierarchy. One of the key features needed in Grid Computing is to maintain up-to-date information about resources and services. Two important parameters that must be selected are the information refresh and expiration times. In this work, R is presented for studying the relation between these important parameters in three policies: Hierarchical, Super-peer and Random. The results reveal an interesting relation between expiration and refresh times in all studied policies. The study of this new parameter is essential to provide a deeper knowledge in new information distribution policies and in the configuration or deployment of existing ones.